Integrated Metabolomic and Transcriptomic Analysis Reveals the Effect of Artificial Shading on Reducing the Bitter Taste of Bamboo Shoots - Yongjian Huang; Hang Xun; Guilin Yi; Ti Li; Xi Yao; Feng Tang (Horticulturae, 2022)
Bamboo shoot is a delicious and nutritious forest vegetable. It has been found that bamboo shoots collected from low-light environments have a less bitter taste. The molecular mechanism of light in the regulation of bitter substance accumulation in bamboo shoots is still unclear. In this study, we applied a shading treatment to Pleioblastus amarus bamboo shoots in the preharvesting period. The reduction in the bitterness intensity was confirmed by a sensory test. An integrated metabolomic and transcriptomic analysis was performed on P. amarus bamboo shoots grown under shading treatment and normal growing conditions, and 56 differentially accumulated metabolites and 178 differentially expressed genes were identified. The results showed that the contents of a series of phenolic acids related to the tyrosine metabolism pathway were downregulated under shading treatment, revealing that shading decreased the accumulation of phenolic acids and further mediated the resulting bitter taste of the bamboo shoots. This work will be helpful for understanding the regulatory mechanisms governing the bitter tasting substances in bamboo shoots grown under a shading treatment and provides a reference for the use of shading treatment in cultivation practices to improve the taste of bamboo shoots.